Safety measurement and monitoring in healthcare: a framework to guide clinical teams and healthcare organisations in maintaining safety - Vincent, Charles (BMJ Publishing Group, 2014)
Patients, clinicians and managers all want to be reassured that their healthcare organisation is safe. But there is no consensus about what we mean when we ask whether a healthcare organisation is safe or how this is achieved. In the UK, the measurement of harm, so important in the evolution of patient safety, has been neglected in favour of incident reporting. The use of softer intelligence for monitoring and anticipation of problems receives little mention in official policy. The Francis Inquiry report into patient treatment at the Mid Staffordshire NHS Foundation Trust set out 29 recommendations on measurement, more than on any other topic, and set the measurement of safety an absolute priority for healthcare organisations. The Berwick review found that most healthcare organisations at present have very little capacity to analyse, monitor or learn from safety and quality information. This paper summarises the findings of a more extensive report and proposes a framework which can guide clinical teams and healthcare organisations in the measurement and monitoring of safety and in reviewing progress against safety objectives. The framework has been used so far to promote self-reflection at both board and clinical team level, to stimulate an organisational check or analysis in the gaps of information and to promote discussion of ‘what could we do differently’.